The Descriptive Study of Gresik Cements Product Quality: Survey on Gresik Cements Users in Surabaya - Felly Febianto; Koespiadi (NAROTAMA UNIVERSITY, Indonesia, 2021)
Cement is a product that is needed in the construction of infrastructure and various kinds of buildings. The function of cement as an adhesive material in the building construction makes cement have a vital position for people. Therefore, cement producers must pay attention to the quality of cement produced to fulfill the cement supply in accordance with development needs, either quantity or quality. There are many cement producers and brands in the market, makes people have many choices of cement products that can be used. This study aims to examine the quality of Gresik cement on cement users in Rungkut District, Surabaya. The research method used is descriptive quantitative research. Data was collected by spreading questionnaire to 79 cement users who are construction workers in Rungkut District, Surabaya. These data is then processed by applying descriptive statistics supported by SPSS for Windows version 20.0 program. The results reveals that the quality of Gresik cement was categorized as good. The highest quality perceived by respondents is reliability, followed by conformance to specifications and product performance. Meanwhile, aspects that are perceived as lower by users are durability, aesthetics, and additional features.